Improving Organizational Performance Assessment through the Balanced Scorecard Approach at PERUMDAM Tirta Mukti Cianjur Regency - Fitri, Risa Estiya; Octavia, Evi (Electronic Journal of Education, Social Economics and Technology, 2025)
This research aims to analyze the performance of the Regional Drinking Water Company (PERUMDAM) Tirta Mukti in Cianjur Regency using the Balanced Scorecard (BSC) approach, which consists of four main perspectives: financial, customer, internal business processes, and learning and growth. This study uses a descriptive quantitative approach with data collected through documentation and interviews with employees, as well as internal company document analysis. The results show that from the financial perspective, PERUMDAM Tirta Mukti has maintained financial stability through increased operational revenue and efficient cost management. From the customer perspective, there has been an improvement in service coverage and active customer growth, although customer loyalty still requires strengthening. In terms of internal business processes, the company has successfully reduced water loss and maintained stable service hours. Meanwhile, in the learning and growth perspective, there has been a significant increase in employee training and training cost ratios, reflecting the company’s commitment to improving human resource quality. Overall, PERUMDAM Tirta Mukti's performance is categorized as “healthy” based on the Ministry of Public Works and Housing (PUPR) indicators (2021). The Balanced Scorecard approach proves effective in providing a comprehensive overview of strategic performance in regional water service companies.